Perilaku Narsisme pada Remaja Pengguna Media Sosial - Kimmy Katkar; Dian Wishnu Brata; Anna Dian Savitri (Neolectura, 2021)
This research aims to determine the phenomenon of narcissistic behavior among adolescent social media users. Respondents who are the subjects in this study are adolescents aged 16 to 20 years who live in the Mranggen sub-district, Demak district who have more than three social media accounts that have been used for more than 1 year, and carry out activities on their social media every day. The method used in this research is a qualitative method with a phenomenological approach. Methods of data collection using interviews and documentation which are arranged based on the characteristics of narcissism. As for the data analysis technique that will be used is descriptive coding method. The results of the study show that the subject often shows a thing or situation that encourages other people to have a good impression by minimizing things that are negative or not good for themselves